E-GP Implementations : A Review of Business Models and Approaches - World Bank (Washington, DC, 2014)
E-procurement systems have become an integral component of procurement reform by governments around the world as they move to institute competitive and fully transparent procurement systems, and to address issues of corruption and transparency. This rise in demand for e-Government Procurement (e-GP) systems has created an innovative industry of technical products and business arrangements. To support the development, implementation and operation of e-procurement systems, governments have undertaken several different business approaches, from complete in house solutions to various types of third-party partnerships. Each implementation has its own set of benefits and business issues associated with it, which directly affect both the government and the suppliers doing business with the government. The purpose of the study is to identify the types of business arrangements used by governments; the benefits of these arrangements; how they may or may not affect the procurement process; the types of issues or perceived issues that have resulted from the business approaches applied; the contractual arrangements or policies that have been drafted to mitigate issues and ensure the integrity and security of the procurement process. The goal of this study is to continue expanding the World Bank knowledge base on e-procurement programs, approaches and solutions so that it can continue to assist organizations with the implementation and management of new and current government e-procurement initiatives.